Sticky costs in the classroom: Rethinking management accounting education for real-world financial challenges - Lucas, A.; Azevedo, G.; Oliveira, J.; Santos, L. L. (INTED2025 Proceedings, 2025)
In recent years, research on cost behavior in accounting has advanced significantly, particularly with the introduction of the concept of “sticky costs.” These costs exhibit asymmetry, meaning they increase more rapidly with rising activity levels than they decrease with falling activity. This phenomenon challenges cost management as it complicates earnings predictability and financial stability for organizations. While the concept has gained traction in management accounting literature, its integration into higher education curricula, specifically in degree programs in accounting and management, remains limited. This study aims to analyze the incorporation of the sticky costs concept into the curricula of management accounting courses within degrees in management and accounting at Portuguese universities. The empirical research will involve analyzing the course syllabi to assess how topics related to the asymmetrical behavior of costs are addressed, either explicitly or implicitly, and to determine how these concepts can be better integrated into academic programs to enrich student learning. The study will evaluate the extent to which new theoretical approaches to cost behavior are integrated into the curriculum, comparing them with traditional models that classify costs as either fixed or variable. Furthermore, this research will explore the pedagogical implications of teaching sticky costs within management accounting curricular units, discussing how this knowledge can improve students’ understanding of the cost dynamics within real-world organizations. The study will also assess whether properly addressing sticky costs can better prepare students to tackle the complex financial challenges faced by organizations, particularly in today’s dynamic economic environments. This study also contributes to the broader conversation around the United Nations Sustainable Development Goals (SDGs), specifically SDG 4, which aims to ensure inclusive, equitable, and quality education for all. By integrating concepts such as sticky costs into management accounting curricula, the study seeks to promote a more relevant and practical education, equipping students with a deeper understanding of the financial challenges organizations face. Furthermore, by addressing the financial sustainability of organizations, this research indirectly supports SDG 8, which aims to promote sustained, inclusive, and sustainable economic growth, as well as increased productivity and decent work. The proposed curriculum updates not only enhance the quality of education in management accounting but also reinforce the role of higher education institutions as agents of change, fostering more responsible business practices aligned with global sustainability goals. This research will contribute to improving the academic formation of future professionals in accounting and management, providing both theoretical insights and practical recommendations for curriculum design. Ultimately, it seeks to align educational practices with the evolving needs of the business world, ensuring that students are equipped with the tools necessary for navigating complex financial landscapes and contributing to sustainable economic development.